Identity and Ethnicity in John Agard’s Poetry: A Critical Discourse Analysis - Al-Mamoory, Dr. Salih Mahdi; Rahi, Hawraa Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
Identity and ethnicity attract the attention of most, if not all, discourse analysts for their importance in squeezing the ideology behind using certain linguistic constructions. The present study is an endeavour to plant a critical seed in the land of the poetry of the British poet, John Agard, to examine his language, mainly in his well-know poem "Half-Caste". It, therefore, basically aims at identifying the structure of the analytical framework of poetry from a critical discourse perspective as far as Agard’s poetry is concerned. In accordance with its aims, this study hypothesises that the structure of the analytical framework of poetry is mapped in terms of three dimensions which are the structure of the poem, the textual analysis, and the social practice from a critical discourse perspective. For the sake of achieving its aims and testing the validity of its hypotheses, the present study follows certain steps. It mainly reviews the relevant literature about critical discourse analysis, the theme of the poem, its poet, and other critical issues. Moreover, it analyses the poem "Half-Caste" as a representative example via a model developed in the present study for this purpose. The present study has arrived at a diversity of conclusions, the most essential of them is that the structure of the analytical framework of poetry is mapped in terms of three dimensions: the structure of the poem, the textual analysis, and the social practice from a critical discourse perspective to show the fluidity of identity and the roughness of ethnicity.